Polymer mortar capable of being quickly dried as well as preparation method and application of polymer mortar
By improving the hydration reaction speed of polymer mortar and fully automated production process, the problems of uneven surface and long curing time during the solidification of traditional polymer mortar are solved, rapid drying and efficient production are achieved, and factory production efficiency is improved .
Patent Information
- Application Number
- CN202411483444.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-23
- Publication Date
- 2025-01-07
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The uneven shrinkage stress generated by traditional polymer mortar during solidification causes uneven surfaces of the waterproof backing plate, affecting construction quality, and long maintenance time, affecting factory production efficiency.
Rapid drying polymer mortar prepared using raw materials such as cement, sand, acrylic emulsion, S105 ore powder, hydrophobic agent, defoaming agent and hydroxypropyl methylcellulose ether. The polymer mortar is made by improving the hydration reaction speed. Rapid solidification in a thermal environment, combined with fully automated production processes and grid cloth covering technology, ensures smooth and rapid drying of the surface.
It realizes rapid solidification and efficient production of polymer mortar, improves factory production speed, and maintains the later strength and surface flatness of the mortar, shortens the maintenance time.
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of building materials, and more specifically to a polymer mortar capable of being dried quickly, and a preparation method and application thereof. Background Art
[0002] Extruded board is one of the most commonly used thermal insulation materials in the building decoration industry, but its disadvantages are low tensile strength, flammability and easy deformation. In order to improve these disadvantages, some manufacturers have coated polymer mortar on both sides of extruded board in recent years to make waterproof backing boards, which are widely used in moisture-proofing, thermal insulation, heat insulation of interior and exterior walls of buildings, wall and floor substrates, and waterproofing.
[0003] Since traditional polymer mortar cannot guarantee the strength and flexibility required by waterproof backing boards, when the first side of the polymer mortar solidifies, the stress generated by shrinkage causes the board surface to deform, which is specifically manifested as warping on both sides. When the second side of the polymer mortar solidifies, shrinkage stress will also be generated, but the shrinkage stress generated on the first and second sides are not exactly the same, so the shrinkage of the second side cannot offset the stress of the first side when it shrinks, which causes the surface of the waterproof backing board to be uneven, and the uneven surface of the waterproof backing board will directly affect the flatness of the wall after construction; and the curing time is long, usually single-sided steam curing requires 8 hours, and natural curing requires 1 to 7 days, so the time and cycle of double-sided curing are even longer.
[0004] Therefore, high-performance polymer mortars have been gradually developed, and polymer-modified polymer mortars with better bonding properties have developed rapidly, with great improvements in performance and variety. Due to the needs of factory production scenarios, polymer mortars that can be dried quickly have become an urgent problem that needs to be solved. The main components of polymer mortars that can be dried quickly are cement, aggregates and organic polymers that can be dispersed in water. Compared with traditional polymer mortars, they have good crack resistance, impermeability and thermal sensitivity, and have the characteristics of large production capacity and simple operation for factory production of mortar products. Summary of the invention
[0005] In view of this, the present invention proposes a polymer mortar that can be dried quickly and a preparation method thereof, comprising the following raw materials in parts by weight: 200-300 parts of cement, 400-600 parts of sand, 60-120 parts of acrylic emulsion, 40-80 parts of S105 mineral powder, 1-1.5 parts of water repellent, 2-3 parts of defoamer, 3-5 parts of mortar enhancer, and 1-3 parts of hydroxypropyl methylcellulose ether. The present invention can effectively improve the hydration reaction speed of the polymer mortar, so that the polymer mortar can solidify quickly in a hot environment, which helps to improve the factory production speed without affecting the later strength of the mortar.
[0006] A polymer mortar capable of being dried quickly, characterized in that it comprises the following raw materials in parts by weight: 200-300 parts of cement, 400-600 parts of sand, 60-120 parts of acrylic emulsion, 40-80 parts of S105 mineral powder, 1-1.5 parts of water repellent, 2-3 parts of defoamer, 3-5 parts of mortar strengthener, and 1-3 parts of hydroxypropyl methylcellulose ether.
[0007] Furthermore, the mortar enhancer is composed of sodium sulfoaluminate, bentonite and water. The sodium sulfoaluminate is ground into ultrafine powder, added with water at a ratio of 1:5 to dissolve for 24 hours, and the same proportion of bentonite is added and stirred evenly.
[0008] Furthermore, the mortar enhancer is ready for use after being prepared, and the storage time shall not exceed 8 hours.
[0009] Furthermore, the activity of the hydroxypropyl methylcellulose ether is 200,000 units.
[0010] Furthermore, the mass fraction of the acrylic emulsion is 6-12%, and the water repellent is silicone-based, with an addition amount of 0.1%-0.15%.
[0011] Furthermore, the S105 mineral powder is selected with high activity and a fineness of 25-35 μm.
[0012] Furthermore, the acrylic emulsion is styrene acrylic, and its solid content is 48%.
[0013] Furthermore, the cement is silicate cement; the sand is mud-free quartz sand; and the defoaming agent is a polymer active material.
[0014] A method for preparing a polymer mortar that can be dried quickly, characterized in that it comprises the following steps:
[0015] Step 1: Grind sodium sulfoaluminate into ultrafine powder, add water in a ratio of 1:5 to dissolve for 24 hours, add bentonite in the same proportion and stir evenly to prepare a mortar reinforcing agent;
[0016] Step 2: Add a certain amount of water to the high-speed disperser and stir. While stirring, slowly and evenly add cement to mix evenly to form a cement solution;
[0017] Step 3: S105 mineral powder, hydroxypropyl methylcellulose ether, water repellent, and defoamer are accurately measured and dry-mixed with sand and then mixed evenly. Subsequently, the mixture is slowly and evenly added to the cement solution of step 2 while stirring, and mixed evenly to prepare a cement mixture;
[0018] Step 4: Add a quantitative mortar strengthener and acrylic emulsion to the cement mixture formed in step 3, stir the slurry for 15 minutes, and prepare a polymer mortar, wherein the mortar strengthener is prepared in step 1.
[0019] A fully automated production process for a waterproof backing board using the polymer mortar is characterized by comprising the following steps:
[0020] Step 1: trim the waterproof backboard so that the overall structure of the waterproof backboard is a rectangle;
[0021] Step 2: placing the trimmed waterproof backboard on the loading platform and conveying it to the first mesh cloth covering device through the first part, the second part and the third part of the first conveyor belt in sequence to cover the upper surface of the trimmed waterproof backboard with mesh cloth, the conveying speed of the loading platform is V1, and the conveying speeds of the first part, the second part and the third part of the first conveyor belt are V2, V3 and V4 respectively, and V1>V2>V3>V4, so that when multiple trimmed waterproof backboards are conveyed to the first mesh cloth covering device through the first part, the second part and the third part of the first conveyor belt in sequence, adjacent side surfaces are in contact with each other to form a seamless whole, thereby preventing the polymer mortar from falling onto the first conveyor belt when the polymer mortar is sprayed on the trimmed waterproof backboard, causing malfunctions to the conveyor belt and subsequent operation;
[0022] Step 3: quantitatively spraying the upper surface of the waterproof backboard covered with the mesh cloth through a first polymer mortar spraying device;
[0023] Step 4: Scrape the sprayed waterproof backboard until the surface of the waterproof backboard is flat;
[0024] Step 5: The waterproof backboard after scraping is rapidly dried with hot air at 50°C to 70°C to form a polymer mortar layer;
[0025] Step 6: Keep the mortar layer on the upper surface of the waterproof backboard after drying at 40°C to 60°C, and flip the semi-finished product 180° at this temperature. Since the surface temperature of the mortar layer is 40°C to 60°C at this time, the polymer mortar layer is relatively soft and can be flipped, so that the upper and lower surfaces are swapped so that the physical positions of the upper and lower surfaces of the waterproof backboard are interchanged, and when passing through the second conveyor belt to the second mesh cloth covering device in turn, since the mesh cloth on the upper surface of the waterproof backboard has been bonded to the upper surface of the waterproof backboard by the dried polymer mortar, the mesh cloth makes the adjacent sides of the waterproof backboard still in a state of abutting each other after flipping 180°, thereby preventing the polymer mortar from falling onto the second conveyor belt when the trimmed waterproof backboard is sprayed with the polymer mortar, causing malfunctions to the conveyor belt and subsequent operation;
[0026] Step 7: quantitatively spray the lower surface of the waterproof backboard covered with the mesh cloth through the second polymer mortar spraying equipment, scrape the waterproof backboard after spraying, and then rapidly hot-air dry the scraped waterproof backboard at 50° C. to 70° C. to form a polymer mortar layer;
[0027] Step 8: Cut and stack the waterproof backboards with the upper and lower surfaces sprayed with dried polymer mortar.
[0028] Furthermore, in step 2 or step 6, the mesh cloth is a warp-knitted square or rectangular mesh cloth. When the polymer mortar is sprayed, the polymer mortar will enter the bottom of the mesh cloth through the fully covered square holes or rectangular holes, so that the mesh cloth floats to 1 / 3 of the thickness of the polymer mortar. The polymer mortar fixes the mesh cloth on the upper surface or lower surface of the waterproof backboard. The fully covered squares or rectangles make it difficult for the polymer mortar to overflow.
[0029] Furthermore, the transmission speed of the third portion of the first conveyor belt and the second conveyor belt is 5 m / min to 10 m / min.
[0030] Furthermore, the transmission speed V1 of the loading platform is 6m / min to 12m / min, the transmission speed V2 of the first part of the first section of the conveyor belt is 5m / min to 10m / min, and the transmission speed V3 of the second part of the second section of the conveyor belt is 6m / min to 12m / min.
[0031] Furthermore, the mesh cloth is made of glass fiber and has been treated to be alkali-resistant.
[0032] Furthermore, the mesh cloth has a thickness of 0.2-0.3 mm.
[0033] Furthermore, the thickness of the polymer mortar layer on the upper surface or the lower surface of the waterproof backboard after drying is 1.0-2 mm, and the preferred thickness of the polymer mortar layer is 1.2 mm.
[0034] Beneficial effects of the present invention:
[0035] The present invention provides a polymer mortar that can be dried quickly and a preparation method thereof, comprising the following raw materials in parts by weight: 200-300 parts of cement, 400-600 parts of sand, 60-120 parts of acrylic emulsion, 40-80 parts of S105 mineral powder, 1-1.5 parts of water repellent, 2-3 parts of defoamer, 3-5 parts of mortar enhancer, and 1-3 parts of hydroxypropyl methylcellulose ether. The present invention can effectively improve the hydration reaction speed of the polymer mortar, so that the polymer mortar can solidify quickly in a hot environment, which helps to improve the factory production speed without affecting the later strength of the mortar. DETAILED DESCRIPTION
[0036] Example 1
[0037] A polymer mortar capable of drying quickly comprises the following raw materials in parts by weight: 300 parts of cement, 510 parts of sand, 100 parts of acrylic emulsion, 80 parts of S105 mineral powder, 1.5 parts of water repellent, 2.5 parts of defoamer, 4 parts of mortar reinforcing agent, and 2 parts of hydroxypropyl methylcellulose ether. The mortar reinforcing agent consists of sodium sulfoaluminate, bentonite, and water. The sodium sulfoaluminate is ground into ultrafine powder, added with water in a ratio of 1:5 to dissolve for 24 hours, and bentonite in the same proportion is added and stirred evenly. The mortar reinforcing agent is ready for use. The storage time shall not exceed 8 hours. The activity of the hydroxypropyl methylcellulose ether is 200,000 units. The mass fraction of the acrylic emulsion is 6-12%. The hydrophobic agent is silicone and the addition amount is 0.1%-0.15%. The S105 mineral powder is highly active and has a fineness of 25-35 μm. The acrylic emulsion is styrene-acrylic and has a solid content of 48%. The cement is silicate cement; the sand is mud-free quartz sand; and the defoaming agent is a polymer active material.
[0038] Comparative Example
[0039] A polymer mortar that cannot be dried quickly comprises the following raw materials in parts by weight: 300 parts of cement, 550 parts of sand, 19 parts of dispersible latex powder, 1.5 parts of water repellent, 2.5 parts of defoamer, 125 parts of fly ash, and 2 parts of hydroxypropyl methyl cellulose ether, wherein the activity of the hydroxypropyl methyl cellulose ether is 200,000 units, the water repellent is organic silicon, the fly ash is selected to have high activity and a fineness of 25-35 μm, the cement is silicate cement, the sand is mud-free quartz sand, and the defoamer is a high-molecular active material.
[0040] Through testing, the polymer mortar capable of rapid drying of the present application can complete 90% drying in 6 minutes for every 1mm thickness under 70°C hot air condition, while the cement mortar prepared in the comparative example cannot complete solidification under 70°C hot air condition and will lose water and powderize.
[0041] Example 2
[0042] A method for preparing a polymer mortar that can be dried quickly, characterized in that it comprises the following steps:
[0043] Step 1: Grind sodium sulfoaluminate into ultrafine powder, add water in a ratio of 1:5 to dissolve for 24 hours, add bentonite in the same proportion and stir evenly to prepare a mortar reinforcing agent;
[0044] Step 2: Add a certain amount of water to the high-speed disperser and stir. While stirring, slowly and evenly add cement to mix evenly to form a cement solution;
[0045] Step 3: S105 mineral powder, hydroxypropyl methylcellulose ether, water repellent, and defoamer are accurately measured and dry-mixed with sand and then mixed evenly. Subsequently, the mixture is slowly and evenly added to the cement solution of step 2 while stirring, and mixed evenly to prepare a cement mixture;
[0046] Step 4: Add a quantitative mortar strengthener and acrylic emulsion to the cement mixture formed in step 3, stir the slurry for 15 minutes, and prepare a polymer mortar, wherein the mortar strengthener is prepared in step 1.
[0047] Example 3
[0048] A fully automated production process for a waterproof backing board using the polymer mortar is characterized by comprising the following steps:
[0049] Step 1: trim the waterproof backboard so that the overall structure of the waterproof backboard is a rectangle;
[0050] Step 2: placing the trimmed waterproof backboard on the loading platform and conveying it to the first mesh cloth covering device through the first part, the second part and the third part of the first conveyor belt in sequence to cover the upper surface of the trimmed waterproof backboard with mesh cloth, the conveying speed of the loading platform is V1, and the conveying speeds of the first part, the second part and the third part of the first conveyor belt are V2, V3 and V4 respectively, and V1>V2>V3>V4, so that when multiple trimmed waterproof backboards are conveyed to the first mesh cloth covering device through the first part, the second part and the third part of the first conveyor belt in sequence, adjacent side surfaces are in contact with each other to form a seamless whole, thereby preventing the polymer mortar from falling onto the first conveyor belt when the polymer mortar is sprayed on the trimmed waterproof backboard, causing malfunctions to the conveyor belt and subsequent operation;
[0051] Step 3: quantitatively spraying the upper surface of the waterproof backboard covered with the mesh cloth through a first polymer mortar spraying device;
[0052] Step 4: Scrape the sprayed waterproof backboard until the surface of the waterproof backboard is flat;
[0053] Step 5: The waterproof backboard after scraping is rapidly dried with hot air at 50°C to 70°C to form a polymer mortar layer;
[0054] Step 6: Keep the mortar layer on the upper surface of the waterproof backboard after drying at 40°C to 60°C, and flip the semi-finished product 180° at this temperature. Since the surface temperature of the mortar layer is 40°C to 60°C at this time, the polymer mortar layer is relatively soft and can be flipped, so that the upper and lower surfaces are swapped so that the physical positions of the upper and lower surfaces of the waterproof backboard are interchanged, and when passing through the second conveyor belt to the second mesh cloth covering device in turn, since the mesh cloth on the upper surface of the waterproof backboard has been bonded to the upper surface of the waterproof backboard by the dried polymer mortar, the mesh cloth makes the adjacent sides of the waterproof backboard still in a state of abutting each other after flipping 180°, thereby preventing the polymer mortar from falling onto the second conveyor belt when the trimmed waterproof backboard is sprayed with the polymer mortar, causing malfunctions to the conveyor belt and subsequent operation;
[0055] Step 7: quantitatively spray the lower surface of the waterproof backboard covered with the mesh cloth through the second polymer mortar spraying equipment, scrape the waterproof backboard after spraying, and then rapidly hot-air dry the scraped waterproof backboard at 50° C. to 70° C. to form a polymer mortar layer;
[0056] Step 8: Cut and stack the waterproof backboards with the upper and lower surfaces sprayed with dried polymer mortar.
[0057] Furthermore, in step 2 or step 6, the mesh cloth is a warp-knitted square or rectangular mesh cloth. When the polymer mortar is sprayed, the polymer mortar will enter the bottom of the mesh cloth through the fully covered square holes or rectangular holes, so that the mesh cloth floats to 1 / 3 of the thickness of the polymer mortar. The polymer mortar fixes the mesh cloth on the upper surface or lower surface of the waterproof backboard. The fully covered squares or rectangles make it difficult for the polymer mortar to overflow.
[0058] Furthermore, the transmission speed of the third portion of the first conveyor belt and the second conveyor belt is 5 m / min to 10 m / min.
[0059] Furthermore, the transmission speed V1 of the loading platform is 6m / min to 12m / min, the transmission speed V2 of the first part of the first section of the conveyor belt is 5m / min to 10m / min, and the transmission speed V3 of the second part of the second section of the conveyor belt is 6m / min to 12m / min.
[0060] Furthermore, the mesh cloth is made of glass fiber and has been treated to be alkali-resistant.
[0061] Furthermore, the mesh cloth has a thickness of 0.2-0.3 mm.
[0062] Furthermore, the thickness of the polymer mortar layer on the upper surface or the lower surface of the waterproof backboard after drying is 1.0-2 mm, and the preferred thickness of the polymer mortar layer is 1.2 mm.
[0063] Beneficial effects of the present invention:
[0064] The present invention provides a polymer mortar that can be dried quickly and a preparation method thereof, comprising the following raw materials in parts by weight: 200-300 parts of cement, 400-600 parts of sand, 60-120 parts of acrylic emulsion, 40-80 parts of S105 mineral powder, 1-1.5 parts of water repellent, 2-3 parts of defoamer, 3-5 parts of mortar enhancer, and 1-3 parts of hydroxypropyl methylcellulose ether. The present invention can effectively improve the hydration reaction speed of the polymer mortar, so that the polymer mortar can solidify quickly in a hot environment, which helps to improve the factory production speed without affecting the later strength of the mortar.
[0065] The above-mentioned embodiments only express several implementation methods of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the patent of the present invention. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A polymer mortar capable of rapid drying, characterized in that: The raw materials include the following parts by weight: 200-300 parts of cement, 400-600 parts of sand, 60-120 parts of acrylic emulsion, 40-80 parts of S105 mineral powder, 1-1.5 parts of water repellent parts, defoamer 2-3 parts, mortar enhancer 3-5 parts, hydroxypropyl methylcellulose ether 1-3 parts.
2. The polymer mortar capable of rapid drying according to claim 1, characterized in that: The mortar enhancer is composed of sodium sulfoaluminate, bentonite and water. The sodium sulfoaluminate is ground into ultrafine powder, added with water in a ratio of 1:5 to dissolve for 24 hours, and then the bentonite in the same proportion is added and stirred evenly.
3. The polymer mortar capable of rapid drying according to claim 1, characterized in that: The mortar enhancer can be used immediately after preparation and the storage time shall not exceed 8 hours.
4. The polymer mortar capable of rapid drying according to claim 1, characterized in that: The activity of the hydroxypropyl methylcellulose ether is 200,000 units.
5. The polymer mortar capable of rapid drying according to claim 1, characterized in that: The mass fraction of the acrylic emulsion is 6-12%, and the water repellent is silicone-based, with an addition amount of 0.1%-0.15%.
6. The polymer mortar capable of rapid drying according to claim 1, characterized in that: The S105 mineral powder is selected with high activity and a fineness of 25-35 μm.
7. The polymer mortar capable of rapid drying according to claim 1, characterized in that: The acrylic emulsion is styrene-acrylic and has a solid content of 48%.
8. The polymer mortar capable of rapid drying according to claim 1, characterized in that: The cement is silicate cement; the sand is mud-free quartz sand; and the defoaming agent is a high-molecular active material.
9. A method for preparing the polymer mortar capable of rapid drying according to claim 1, characterized in that: The following steps are involved: Step 1: Grind sodium sulfoaluminate into ultrafine powder, add water in a ratio of 1:5 to dissolve for 24 hours, add bentonite in the same proportion and stir evenly to prepare a mortar reinforcing agent; Step 2: Add a certain amount of water to the high-speed disperser and stir. While stirring, slowly and evenly add cement to mix evenly to form a cement solution; Step 3: S105 mineral powder, hydroxypropyl methylcellulose ether, water repellent, and defoamer are accurately measured and dry-mixed with sand and then mixed evenly. Subsequently, the mixture is slowly and evenly added to the cement solution of step 2 while stirring, and mixed evenly to prepare a cement mixture; Step 4: Add a quantitative mortar strengthener and acrylic emulsion to the cement mixture formed in step 3, stir the slurry for 15 minutes, and prepare a polymer mortar, wherein the mortar strengthener is prepared in step 1.
10. A fully automated production process for waterproof backing board using the polymer mortar capable of rapid drying as claimed in any one of claims 1 to 8, characterized in that: The following steps are included: Step 1: trim the waterproof backboard so that the overall structure of the waterproof backboard is a rectangle; Step 2: placing the trimmed waterproof backboard on the loading platform and conveying it to the first mesh cloth covering device through the first part, the second part and the third part of the first conveyor belt in sequence to cover the upper surface of the trimmed waterproof backboard with mesh cloth, the conveying speed of the loading platform is V1, and the conveying speeds of the first part, the second part and the third part of the first conveyor belt are V2, V3 and V4 respectively, and V1>V2>V3>V4, so that when multiple trimmed waterproof backboards are conveyed to the first mesh cloth covering device through the first part, the second part and the third part of the first conveyor belt in sequence, adjacent side surfaces are in contact with each other to form a seamless whole, thereby preventing the polymer mortar from falling onto the first conveyor belt when the polymer mortar is sprayed on the trimmed waterproof backboard, causing malfunctions to the conveyor belt and subsequent operation; Step 3: quantitatively spraying the upper surface of the waterproof backboard covered with the mesh cloth through a first polymer mortar spraying device; Step 4: Scrape the sprayed waterproof backboard until the surface of the waterproof backboard is flat; Step 5: The waterproof backboard after scraping is rapidly dried with hot air at 50°C to 70°C to form a polymer mortar layer; Step 6: Keep the mortar layer on the upper surface of the waterproof backboard after drying at 40°C to 60°C, and flip the semi-finished product 180° at this temperature. Since the surface temperature of the mortar layer is 40°C to 60°C at this time, the polymer mortar layer is relatively soft and can be flipped, so that the upper and lower surfaces are swapped so that the physical positions of the upper and lower surfaces of the waterproof backboard are interchanged, and when passing through the second conveyor belt to the second mesh cloth covering device in turn, since the mesh cloth on the upper surface of the waterproof backboard has been bonded to the upper surface of the waterproof backboard by the dried polymer mortar, the mesh cloth makes the adjacent sides of the waterproof backboard still in a state of abutting each other after flipping 180°, thereby preventing the polymer mortar from falling onto the second conveyor belt when the trimmed waterproof backboard is sprayed with the polymer mortar, causing malfunctions to the conveyor belt and subsequent operation; Step 7: quantitatively spray the lower surface of the waterproof backboard covered with the mesh cloth through the second polymer mortar spraying equipment, scrape the waterproof backboard after spraying, and then rapidly hot-air dry the scraped waterproof backboard at 50° C. to 70° C. to form a polymer mortar layer; Step 8: Cut and stack the waterproof backboards with the upper and lower surfaces sprayed with dried polymer mortar.
Citation Information
Patent Citations
Polymer emulsion modified rapid repair mortar and preparation method thereof
CN101857416A
Polymer quick-hardening cement mortar and method for quick repair of waterproof coil concrete protecting layer
CN109231935A
Preparation method and application of vertical wire rock wool composite heat preservation and decoration integrated plate
CN114536821A